EDUKASI PEDAGOGI TENTANG URGENSI PENDIDIKAN KELUARGA BAGI ORANG TUA DI DESA TANJUNG BERINGIN - Rezeki Putra Gulo (Jurnal PKM Setiadharma, 2023)
Tanjung Beringin Village is one of the villages in Sungai Laur District, Ketapang Regency, West Kalimantan. Here is where the community service implementation activities are held. Based on the results of observations and surveys conducted, parents in Tanjung Beringin Village still lack understanding and knowledge that instilling Christian values and shaping their children's spirituality is a responsibility that must be prioritized. As a result of the problem, the parents take a less favourable stance and action for the child, namely transferring this noble responsibility to the church (Sunday school) and school (religious teacher). As a form of responsibility and concern, implementing Community Service is present as an answer to these needs. The goal is that parents in Tanjung Beringin Village can become responsible individuals in shaping their family members into a generation that fears God and has noble morals. Implementing this Community Service uses observation, survey, and discussion methods and is supported by literature studies. As for the results obtained from this effort, parents in Tanjung Beringin Village already understand and know how to be responsible individuals in educating their children in truth through family education.